Vliv ústavní léčby na fenomén sebehodnocení pacientů léčících se ze závislosti na oddělení léčby závislostí Psychiatrické nemocnice Kosmonosy - Filipová, Zdeňka (Univerzita Karlova, 1. lékařská fakulta, 2023)
Baseline: Self-esteem is often perceived as an indicator of emotional and mental well-being and life satisfaction. How we perceive ourselves is also important for our environment. Addiction disrupts the attitude towards oneself, and self-esteem becomes problematic. Therefore, it is important to focus on strengthening self-esteem in therapy. Goals: To determine the change in self-esteem of patients undergoing inpatient treatment for addiction at the Department of Addiction Treatment of the Kosmonosy Psychiatric Hospital. To demonstrate the influence of the studied categories (education, occupation, number of treatments and length of addiction) on self-esteem. To compare the change in the subjective perception of psychological quality of life in relation to self-esteem. To analyze the change in psychological and physical health. To recommend possible interventions based on the findings. Methods: This is a quantitative research conducted using questionnaires administered at the beginning and at the end of treatment. The Rosenberg Self-esteem Scale was used to assess self-esteem. The Schwartz Therapy Assessment Scale measuring the psychological aspect of quality of life was used as an additional measure. To assess treatment outcome, the Maudsley Addiction Profile questionnaire was administered,. Východiska: Sebehodnocení bývá vnímáno jako ukazatel emocionálního a duševního pocitu osobní pohody a životní spokojenosti. Jak vnímáme sami sebe je důležité i pro naše okolí. Závislost narušuje postoj k sobě samému a sebehodnocení je pak problematické. Proto je důležité se v rámci terapie zaměřovat na posilování vlastní hodnoty. Cíle: Zjistit změnu v sebehodnocení pacientů, kteří podstupují ústavní léčbu závislosti na oddělení léčby závislostí Psychiatrické nemocnice Kosmonosy. Prokázat vliv zkoumaných kategorií (vzdělání, zaměstnání, počet léčeb a délka závislosti) na sebehodnocení. Porovnat změnu v subjektivním vnímání psychologického pojetí kvality života v souvislosti se sebehodnocením. Analyzovat změnu v psychickém a ...